Multispecialty surgical management of large clavicular tumor: A case report. (August 2022) - Aladaileh, Mohammad; Moran, Tom; Duffy, Austin; Redmond, Karen; O'Briain, David
Abstract: Introduction: Primary and metastatic malignancies of the clavicle are extremely uncommon and difficult to treat. It carries a high morbidity rate. Total or partial claviculectomy is the recommended treatment option. Presentation of case: A 59-year-old male was admitted with a large left clavicular huge mass; biopsy showed poorly differentiated adenocarcinoma. Treatment started with chemoradiotherapy followed by complete excision of the tumor surgically. Discussion: For treating this rare, difficult case, partial claviculectomy performed by a multispecialty team integrating three surgical skill sets: thoracic, ENT, and orthopedic surgeons, yields the best results. Clavicular carcinoma of known primary (CUP) is rare, and chemoradiotherapy showed preferable results in management. Conclusion: MDT reviews with surgeons, radiologists, pathologists, oncologists, and radiation oncologists are required in rare and complex cases of clavicular malignancy. Multispecialty surgical involvement is required for the safe excision of clavicular tumors with appropriate oncologic margins and fewer complications. Highlights: A huge Clavicular tumor is challenging and rare. Multiple specialty surgeons and physicians are needed for resection and treatment. Primary malignancy is rare, and Unknown primary clavicular tumor is extremely rare.